Study on antilung cancer synergistic effect of Shenqi Fuzheng combined with docetaxel. Issue 6 (July 2018) - Wang, Cheng; Yang, Bing; Wu, Yali; Tan, Li; Sun, Zongxi; Ma, Junming; Lu, Yang; Du, Shouying
Abstract : Shenqi Fuzheng (SQFZ) is a traditional Chinese medicine injection for lung cancer that is commonly used in China. It can significantly improve the immunity of patients after chemotherapy and reduce adverse reactions of chemotherapy. In the present study, we pay attention to whether it showed a direct synergistic effect with commonly used chemotherapy drugs, and combined SQFZ with docetaxel to study the effect on cell proliferation of lung carcinoma cell lines, A549 and mouse lung cancer cell. Four-part experiments were used to study the effects of monotherapy and combined pharmacotherapy of these 2 medicines: (1) Thiazolan experiment test on the cellular toxicity effect, (2) the cellular morphology change after administration under confocal microscopy, (3) the inhibitory effect of the 2 drugs on the invasion and migration of lung cancer, and (4) the influence on apoptosis of 2 studied cell lines. The results showed that SQFZ had no cell growth inhibitory effect (Thiazolan experiment) when used alone, whereas when used in combination, it could significantly enhance the cell growth inhibitory effect of lower concentrations of docetaxel. There was obvious difference between the effects of docetaxel alone and that of combination of the 2 drugs in cell morphology from the degree of cell fragmentation, and it also showed significant synergistic effect on docetaxel (0.8–80 μg/L) on cell migration and apoptosis. These results demonstrated that applying SQFZ as an adjuvant of chemotherapeutic drugs to treat cancer has the clinical significance of reducing toxicity and increasing curative effect.